THE ECOCIDE BETWEEN THE ETHICAL IDEAL AND THE LEGAL REALITY - Vladoiu, Nasty Marian; Maria, Amandalin (International Journal of Legal and Social Order, 2025)
Ecocide—the large-scale destruction of ecosystems by the human agent—has gained increasing prominence as an ethical and legal concern in the Anthropocene era. In this paper we explore ecocide at the intersection of moral philosophy and international law, examining how the ethical imperatives of environmental management have faced the limitations of codification and legal application. Drawing on conceptual and doctrinal analysis, in this paper we analyze the normative evolution of ecocide as an emerging international crime, tracing its roots in moral discourse, post-war humanitarian law, and contemporary climate governance. By integrating ethical theories – such as ecological justice, utilitarian environmental ethics, and deontological duty to non-human life – with legal developments from the Rome Statute to the amendments proposed by the Group of Independent Experts (2021), this study identifies a growing gap between ethical aspiration and legal achievement. Comparative and policy analyses show that, despite the growing recognition of environmental damage as a cross-border moral error, international law remains hampered by sovereignty, evidence and political barriers. Through illustrative case studies, including deforestation in the Amazon, oil pollution in the Niger Delta, and environmental damage during the war in Ukraine, this paper elucidates how moral outrage often outweighs legal responsibility. The conclusion calls for a more ethically grounded jurisprudence that reconciles human and ecological rights, transforming ecocide from an aspirational ideal into a concrete legal norm. The concept of ecocide — literally, "killing the house" (from Greek) — emerged in the 1970s amid debates about the environmental devastation of the Vietnam War. However, despite decades of moral support, ecocide remains largely absent from binding international law.